2011
DOI: 10.1002/ejic.201001184
|View full text |Cite
|
Sign up to set email alerts
|

C–F Bond Activation of Highly Fluorinated Molecules at Rhodium: From Model Reactions to Catalysis

Abstract: Rhodium complexes are excellent tools for the activation of aromatic and olefinic carbon–fluorine bonds. C–F bond cleavage reactions are key steps for the derivatization of highly fluorinated compounds via stoichiometric or catalytic reaction pathways. The reaction routes involve hydrodefluorinations, but also the selective introduction of functional groups at distinctive positions, to provide access to new fluorinated building blocks. One can identify two general types of rhodium precursors that can induce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
48
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(49 citation statements)
references
References 238 publications
1
48
0
Order By: Relevance
“…Radius et al reported an initial and exceptional example of a nickelmediated Suzuki-Miyaura cross coupling reaction of perfluorotoluene with aryl boronic acids on using a nickel(II) carbene complex as catalyst [25]. Sandford et al demonstrated that [Pd(PPh 3 ) 4 ] catalyses the derivatization of the electron-poor polyfluoronitrobenzene with aryl boronic acids and esters [17]. In a recent example, Love et al described the application of [(Me) 2 Pt(mSMe 2 ) 2 ] 2 or [Ni(COD) 2 ]/PPh 3 as precatalysts for the functionalization of polyfluorinated arylimines on using boronic acids [39,47].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Radius et al reported an initial and exceptional example of a nickelmediated Suzuki-Miyaura cross coupling reaction of perfluorotoluene with aryl boronic acids on using a nickel(II) carbene complex as catalyst [25]. Sandford et al demonstrated that [Pd(PPh 3 ) 4 ] catalyses the derivatization of the electron-poor polyfluoronitrobenzene with aryl boronic acids and esters [17]. In a recent example, Love et al described the application of [(Me) 2 Pt(mSMe 2 ) 2 ] 2 or [Ni(COD) 2 ]/PPh 3 as precatalysts for the functionalization of polyfluorinated arylimines on using boronic acids [39,47].…”
Section: Introductionmentioning
confidence: 98%
“…Such reaction pathways can involve C-F activation steps, e.g. at palladium, nickel or rhodium [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Thus, hydrodefluorination or cross coupling reactions can provide fluorinated building blocks, which are often not accessible otherwise .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon-fluorine bonds are considered as the most passive organic functionalities [7][8][9] , and their selective activation under mild conditions remains poorly achieved. Although there has been considerable progress in the stoichiometric activation of C-F bonds, the metalcatalysed versions of the process remain relatively scarce 5,[10][11][12][13][14][15][16][17][18][19][20][21] . The simplest modification of the C-F bond is its transformation to the simple C-H bond (hydrodefluorination, HDF), a process that has been mainly limited to fluoroarenes, with very few examples referring to trifluoromethylarenes and other perfluoroalkyl groups 1,[22][23][24][25][26] .…”
mentioning
confidence: 99%
“…Against such a background, we started developing a novel strategy for their preparation from 1, because 1 is an economical bulk organofluorine feedstock for the production of poly(tetrafluoroethylene) and co-polymers with other alkenes [38][39][40]. However, to the best of our knowledge, no catalytic reactions involving 1 had been reported until we reported the first catalytic transformation reaction [41], while homogeneous catalytic reactions involving C-F bond activation have received an increasing amount of attention [42][43][44][45][46][47][48][49][50][51][52][53]. The C-F bond activation reaction of 1 had been achieved only in a few stoichiometric reactions [54][55][56].…”
Section: Introductionmentioning
confidence: 99%